2023
DOI: 10.1108/jocm-05-2022-0154
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 health crisis and family business performance: the moderating effect of family leadership

Abstract: PurposeIn the context of the coronavirus disease 2019 (COVID-19) crisis, this article aims to analyze the resilience of family businesses in a developing country like Cameroon. As such, this study seeks to fill two gaps in the literature: first, by comparing the financial and social performance of family companies with those of non-family companies not listed on the stock exchange, and second, by comparing performance across family-run companies, according to the companies' mode of leadership in Cameroon, a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 87 publications
0
0
0
Order By: Relevance
“…Yu et al (2015) already revealed that corporate social responsibility performance of family firms is higher than their nonfamily counterparts in times of economic crisis because of SEW. In the same line, a recent study verifies that the involvement of the family and their long‐term orientation have been critical in achieving higher financial and social performance compared to nonfamily firms during the COVID‐19 crisis (Sahut et al, 2023). Specifically, family SMEs have shown a greater capacity to adapt their business models during the COVID‐19 crisis with positive effect in their business performance (Brunelli et al, 2023).…”
Section: Hypothesis Developmentmentioning
confidence: 94%
“…Yu et al (2015) already revealed that corporate social responsibility performance of family firms is higher than their nonfamily counterparts in times of economic crisis because of SEW. In the same line, a recent study verifies that the involvement of the family and their long‐term orientation have been critical in achieving higher financial and social performance compared to nonfamily firms during the COVID‐19 crisis (Sahut et al, 2023). Specifically, family SMEs have shown a greater capacity to adapt their business models during the COVID‐19 crisis with positive effect in their business performance (Brunelli et al, 2023).…”
Section: Hypothesis Developmentmentioning
confidence: 94%